PWE-063 Effectiveness of general hypnotherapy and gut-directed hypnotherapy in refractory irritable bowel syndrome. (28th May 2012) - Hegade, V S; Mohammed, N; Barnett, A; Denyer, M
Abstract : Introduction: Irritable bowel syndrome (IBS) is a very common condition, which constitutes up to 50% of Gastroenterology outpatient referrals. Many pharmacological and non-pharmacological treatments are available with variable results. Hypnotherapy is generally reserved for refractory IBS patients. Although there is ample evidence to show the effectiveness of Gut-directed Hypnotherapy (GDH), there are only few studies to support other forms of hypnotherapy especially general hypnotherapy. Aim of this study was to assess the effectiveness of different types of hypnotherapy on refractory IBS patients treated in our institution, a tertiary referral centre. Methods: In our institution, an experienced hypnotherapist assesses refractory IBS patients. Based on their symptoms, patients receive either general hypnotherapy (GH), GDH or both. All patients score their IBS symptoms on IBS Symptom Score sheet [0–10 Likert scale, minimum score 0, maximum 60] first at the baseline (Pre-hypnotherapy score) and then at the end of the hypnotherapy (Immediate Post-hypnotherapy score). Patients also complete Hospital Anxiety and Depression (HAD) score sheet before and after hypnotherapy. We analysed the data of all patients treated with hypnotherapy between February 2009 and December 2011. Follow-up questionnaires were sent to all patients in the post at variable periods after the completion of hypnotherapy to score their current symptoms (Long-term Post-hypnotherapy score). Parametric methods were used for statistical analysis. Results: During the study period, 34 patients (n=34, females 29, mean age 41.5) received hypnotherapy (GH=15, GDH=8, both =11). Average number of hypnotherapy sessions was 4.7 (range 3–6, 1 h/week). Seventeen (50%) patients returned their follow-up questionnaires. Mean duration between the last session of hypnotherapy and completion of the follow-up questionnaire was 16 months (range 5–32). Abstract PWE-063 table 1 shows the main results. Conclusion: Our study suggests that treatment of refractory IBS patients with general hypnotherapy, either alone or in combination with gut-directed hypnotherapy is effective both in short and long term. These results need to be confirmed in prospective randomised controlled studies directly comparing general hypnotherapy against gut-directed hypnotherapy. Competing interests: None declared.